An Analysis Of Grammatical Error In Writing Narrative Text At XI Grade Students Of SMA Negeri 5 Pematang Siantar - Anita Purba; Benarita; Alpriani Yolanda (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
Based on the background of the researcher , the problem can be formulated in the form of questions as follows: How is grammatical error analysis able to explain the ability of eleventh grade students at SMA Negeri 5 PematangSiantar in the 2022/2023 academic year to write narrative text The main objective of this study is to analyze grammatical errors made by students in writing narrative texts. Based on the formulation of the problem above, the researcher focuses on conducting research on analyzing grammatical errors in writing narrative texts. In this research, the researcher employed qualitative research, also known as descriptive research. The researcher used the surface structure taxonomy framework proposed by Dulay, Burt, and Krashen (1982) which categorizes errors into four types: omission, addition, misinformation, and misordering. It is located in the Jalan Medan Km 6,5. KecamatanSiantarMartoba, Kota PematangSiantar.There were 92 errors found by researchers on narrative texts made by 15 students of XI PMIA 1 hat were enough to pass the minimum score..It can be concluded that even though they are students with higher class references considered as students who have better language skills, they can still make errors. The percentage of misinformation was 44%, followed by Omission at 34%, then an additional 15%, and the latter misleading at 7%. From the analysis can be seen that the ability of students is still not perfect in writing narrative text. From this analysis it can be meant that students should be more practical in understanding the use of grammar, to be able to write narrative text to be even better for the future.